2017
DOI: 10.1007/s11418-017-1108-3
|View full text |Cite
|
Sign up to set email alerts
|

Structures of antimutagenic constituents in the peels of Citrus limon

Abstract: The methanolic extracts from the peels of Citrus limon were found to show antimutagenic effects against 3-amino-1,4-dimethyl-5H-pyrido[4,3-b]indole, and 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) in the Ames test. From the methanolic extracts, four new coumarins (wakayamalimonol A-D) and a new furanocoumarin (wakayamalimonol E) were isolated together with fifteen known compounds. The absolute stereostructures of the new compounds were determined by chemical synthesis and the modified Mosher's metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…As a result, limonin (19) and lansionic acid (53) significantly decreased the frequency of micronucleated reticulocytes (MNRETs) treated with PhIP at 24 h and 48 h after the administration ( Fig. 4) [4,7].…”
Section: Evaluation Of the Antimutagenic Effects Of Isolated Compoundmentioning
confidence: 94%
See 4 more Smart Citations
“…As a result, limonin (19) and lansionic acid (53) significantly decreased the frequency of micronucleated reticulocytes (MNRETs) treated with PhIP at 24 h and 48 h after the administration ( Fig. 4) [4,7].…”
Section: Evaluation Of the Antimutagenic Effects Of Isolated Compoundmentioning
confidence: 94%
“…Based on these studies, we searched for antimutagenic materials derived from foods. In the course of this study, we found using the Ames test that the methanolic (MeOH) extracts of C. limon [4,5], aerial parts of I. japonicus [6], and leaves of L. domesticum [7,8] showed antimutagenic effects against Trp-P-1 and PhIP. Therefore, we directed our efforts toward the isolation of their constituents and evaluation of the antimutagenic effects of the isolated constituents using the Ames test and in vivo micronucleus test.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations